Financial Behaviour, Financial Self Efficacy and Intention to Invest in Cryptocurrency - M. Kurnia Rahman Abadi; Hairul Azlan Bin Annuar (University of Darussalam Gontor, 2023)
The Theory of Planned Behaviour is used in this study to investigate the investment intentions of young potential investors in Indonesia. As supplementary dimensions, financial self-efficacy, risk-taking proclivity, and inclination for innovation are offered. A questionnaire-based survey was utilised to collect responses from 276 potential investors, and AMOS and SPSS were used to identify correlations between the components. Financial self-efficacy appears to play a dual function in the association between personality characteristics and investment intention, according to the data. The study only looks at investing intentions, not actual investment behaviour or demographic characteristics. The findings might help financial service providers create